Shaky structures on solid foundation : the impact of low-income state-subsidised housing on the realisation of the right to adequate housing in post-apartheid South Africa - Rafferty, Benjamin (School of Economics, 2016)
This dissertation examines the impact of state-subsidised housing on the realisation of the right to adequate housing in South Africa. The incremental housing policy adopted in 1994 has its roots in the work of the Urban Foundation and others, who significantly shaped the discussions in the National Housing Forum, where South Africa's first post-apartheid housing policy was formulated. As a result low-income housing policy is centred on the use of capital subsidies allocated towards homeownership. In 1996 the state promulgated the Constitution obligating government to ensure that, inter alia, 'everyone has the right of access to adequate housing'. 'Adequate housing', as per the United Nations Covenant on Economic Social and Cultural Rights, comprises of six core elements: accessibility, affordability, location, availability of services, habitability and security of tenure; which have all been affected in various ways by government's legislative and policy interventions. The delivery of state-subsidised housing has been impressive - with nearly three million completed since 1994. However, there have been significant problems. This paper emphasises four main issues: the poor quality houses that have required rectification and/or rebuilding; an overemphasis on homeownership, above rental tenure; a lack of effective transfer of title deeds; and the informal sale of state-subsidised houses. All of which have negatively impacted on progress towards full realisation of the right of access to adequate housing.